MICROPROPAGATION OF BROCCOLI (BRASSICA OLERACEA L.VAR. BOTRYTIS) AND CHANGES OF ENZYME PEROXIDASE, CATALASE, GLUTAMAT DEHYDROGENASE ACTIVITY DURING PLANTLET DEVELOPMENT - Tilaar , Wenny
The aim of this study was to provide Broccoli (B. oleracea L. var. botrytis) seedlings through apical shoot multiplication and organogenesis and to evaluate enzyme activities of peroxidase, catalase and glutamate dehydrogenase during plantlets development. Apical shoot and hypocotyl segments were grown on MS medium supplemented with 0,0; 0,01; 0,1; 1,0 ppm NAA and 0,5; 0,1; 2,5; 5,0 ppm BAP. Increaments of shoot apical on induction medium was two to six shoots per cycle of culture in 14 days. Hypocotyl segments on induction medium produced one to seven adventive shoots in 18 days after planting. The shoot multiplication rate during four times subcultures on MS medium supplemented with 0,5 ppm BAP was 8; 7,5; 8,67 and 7,71 shoots per culture cycle, respectively. The multiplication rate of adventive shoots on hypocotyl segments grown on MS medium supplemented with 0,01 ppm NAA and 2,5 ppm BAP had an average of 13,3; 12,7; 12 and 9,0 shoots per culture cycle.MS medium supplemented with 5 ppm BAP without NAA gave of multiplication rate of average 13; 14,09; 15,89 and 15,14 shoots per culture cycle. Peroxidase activities during apical shoot multiplication were 1,57 to 3,18 times higher than peroxidase activity during seedling stage. The activity during organogenesis of hypocotyl segments were 1,37 to 3, 73 times higher than peroxidase activity of seedling Catalase activity during apical shoot multiplication were 1,03 to 1,49 times higher than catalase activity during seedling stage. The activity of enzyme catalase during organogenesis were 1,05 to 1,5 times higher than the enzyme activity of the seedling. Enzyme activity of glutamate dehydrogenase during shoot multiplication were 0,14 time lower and 1,49 times higher than glutamate dehydrogenase activity of seedling. Glutamate dehydrogenase activity during organogenesis of hypocotyl segments were 0, 13 time lower and 2,54 time higher than the enzyme activity of seedling.